FINANCIAL MANAGEMENT PRACTICES AND PROFITABILITY OF MICRO ENTERPRISES: A SIMPLE ACCOUNTING APPROACH - Eko Muliansyah; Muhammad Hashfi Al Ghazy; Ainul Hajaria; Fitrotun Nida; Muhammad Rafli Saputra; Mush'ab Mush'ab (PT. Jurnal Center Indonesia Publisher, 2026)
Micro enterprises in the Keputih area of Surabaya play an important role in supporting local economic activity, particularly through small-scale food, beverage, and daily-consumption businesses. However, many micro-entrepreneurs still face difficulties in managing their finances systematically. Financial records are often kept manually, inconsistently, or based on memory, making it difficult for business owners to clearly identify cash flow, operating costs, profit levels, and business growth potential. This study aims to analyze the financial management practices of micro enterprises in Keputih, Surabaya, identify the main challenges in applying simple accounting, and examine how basic accounting practices contribute to profitability and business sustainability. This research uses a qualitative approach through direct observation and in-depth interviews with micro-enterprise owners from different business sectors in the Keputih area. The findings show that most business owners have not yet implemented formal accounting systems, but simple practices such as recording daily income, separating business and personal funds, calculating basic costs, and monitoring stock can improve financial control and decision-making. The main obstacles include limited accounting knowledge, lack of discipline in record-keeping, and the perception that small businesses do not require structured financial reports. This study highlights the importance of simple accounting as a practical tool for strengthening profitability, financial awareness, and the sustainability of micro enterprises in local urban communities.